2002
DOI: 10.1128/aem.68.3.1025-1032.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Disinfection of Atypical Mycobacteria Isolated from a Water Distribution System

Abstract: We studied the resistance of various mycobacteria isolated from a water distribution system to chlorine. Chlorine disinfection efficiency is expressed as the coefficient of lethality (liters per minute per milligram) as follows: Mycobacterium fortuitum (0.02) > M. chelonae (0.03) > M. gordonae (0.09) > M. aurum (0.19). For a C · t value (product of the disinfectant concentration and contact time) of 60 mg · min · liter ؊1 , frequently used in water treatment lines, chlorine disinfection inactivates over 4 log … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
129
2
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(145 citation statements)
references
References 41 publications
12
129
2
2
Order By: Relevance
“…NTM often occur in biofilms that form in water supply systems (Falkinham et al 2001;Le Dantec et al 2002a, 2002b. In this study, the Mycobacterium specific 65 kDa heat shock protein gene, an effective target for species differentiation in mycobacteria (Khan and Yadav 2004), was used to determine the diversity of Mycobacterium species in DWDS biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NTM often occur in biofilms that form in water supply systems (Falkinham et al 2001;Le Dantec et al 2002a, 2002b. In this study, the Mycobacterium specific 65 kDa heat shock protein gene, an effective target for species differentiation in mycobacteria (Khan and Yadav 2004), was used to determine the diversity of Mycobacterium species in DWDS biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that Mycobacterium chelonae and Mycobacterium fortuitum were more resistant, whereas Mycobacterium aurum appeared to be the most susceptible mycobacterial species to chlorine. Le Dantec et al (2002a) calculated that chlorination at 0.5 mg·L -1 chlorine for 2 h could eliminate over 4 log units of M. gordonae, but only 1.5 log units of M. fortuitum or M. chelonae. Considering the relatively high level of residual chlorine in water from Guangzhou, M. arupense seems more resistant to chloride than M. gordonae.…”
Section: Discussionmentioning
confidence: 99%
“…hypochiorite solution depends on the concentration of HOCI but not on the total AC concentration (Brazis et al, 1958, Charlton andLevine, 1935;Dantec, et al, 2002;Sagripanti and Bonifacino, 1996). This is attributed to the penetration of HOCl into the microbial cell across the cell wall and membrane.…”
Section: Oxidizing Reactionmentioning
confidence: 99%
“…They pose a particular risk of severe infections in individuals with immunocompromising conditions. Compared to most other bacterial species, mycobacteria are exceptionally resistant to disinfection with chemicals such as chlorine (2,24,33,46). Thus, they may survive chemical treatments at waterworks and enter the distributed water and finally tap water, where their occurrence has been known since the beginning of the 20th century (reviewed by Collins et al [3]).…”
mentioning
confidence: 99%